(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
The influence of impulse neodim lazer radiation on physical-chemical behavior of water and water-micellar solution of anionic surfactants sodium pentadecilsulfat has been studied. It is shown that depending on radiation exposition time the electroconduction of water is changed, which is stipulated by structural changes of water. These changes influence on the process of micellarformation and the meaning of CCM.